Metabolic reprogramming associated with aggressiveness occurs in the G-CIMP-high molecular subtypes of IDH1mut lower grade gliomas - Ruiz-Rodado, Victor; Herold-Mende, Christel (Neuro-Oncology, 2020)
Early detection of increased aggressiveness of brain tumors is a major challenge in the field of neuro-oncology because of the inability of
Published: 30 October 2019
Im Titel ist "mut" hochgestellt
Gesehen am 20.04.2020